The dividend policy and payout ratio dividend decisions: an empirical evidence from employees provident fund Malaysia and Perbadanan Nasional Berhad - Nelson Lajuni; Minah Japang; Jude Woryanta Taunson (Universiti Malaysia Sabah, 2010)
The purpose of this research to analyze the pattern of Employees Provident Fund's and Permodalan Nasional Berhad's dividend payments versus earnings, to observe the trend of dividend distributions of these three government-linked investment companies by looking at the dividend yield and dividend payout ratio, and to analyze the relationship of financial and performance factors with dividend distribution in two important investment institutions in Malaysia namely the Employees Provident Fund (EPF) and Permodalan Nasional Berhad (PNB) through its wholly subsidiary Amanah Saham Nasional Berhad. Additional statistical analyses were presented. The results suggest that government link companies of the surveyed companied have paid dividend during the fifteen years (1985- 2008), whilst the mean of EPS increased from 0.015 in year 2001 to over 0.10 in year 2005 (6 times). An examination of the t-values indicates that GDP did not contribute towards EPF, ASB, and ASN dividend payouts. This finding however indicates several patterns. First, the identified financing patterns put in perspective the exposure of the financial sector to investment-related risks but, against a background of concerns about suboptimal allocation of capital, bring to the fore corporate governance ,dividend policy, and transparency and accountability of public funds. Second, the findings suggest policy adjustments that would help in achieving the government's goals of improving the quality of growth and increasing the role of consumption. Third, long term saving prospects and the impact of financial sector and pension policies are discussed. The findings of the study might be of interest to academicians and practitioners. This paper explores the dividend policy in two important government-linked companies in a fast-growing market that has received inadequate research attention. The paper thus adds to the body of accounting knowledge.